Exilic experiences and creative practice : insights from the lives and art of scholar-artists exiled on Cheju Island during the Choson Dynasty (1392-1910) - Oh, Keumhee (Curtin University, 2012)
The experiences of three scholar artists who are exiled to South Korea’s Cheju Island during the Choson Dynasty is examined with a focus on the conditions of exile they were subjected to and their expressions of mental and physical pain in the form of letters, poetry, paintings and other works of art and literature. Insight from the historical exiles’ experiences and creative practices is hoped to offer a more multi-faceted understanding of Choson exile artists.